Studi Komparatif Makna Konsep Bumi, Dunia dan Alam Semesta - Rilliandi Arindra Putawa (Sekolah Pasca Sarjana IAIN Bengkulu, 2021)
Metaphysical problems in the field of philosophy are not only limited to general things such as existence, reality, or space-time, but there are other problems related to the conception of what humans say as reality that is in front of their eyes. The concept of the earth, the world, and universe are three popular concepts that refer to the set of everything that can be explored by human knowledge. This research is a comparative study that tries to compare the three concepts and try to analyze the relationship between the three concept from a philosophical point of view. The results showed that the concept of the world is a concept that can refer to the other two concepts and has implications for each meaning.